Efficacy and safety of abrocitinib monotherapy in adolescents and adults: a post hoc analysis of the phase 3 JAK1 atopic dermatitis efficacy and safety (JADE) REGIMEN clinical trial - Carsten Flohr; Michael J. Cork; Michael R. Ardern-Jones; Lawrence F. Eichenfield; Sébastien Barbarot; Claire Feeney; Ricardo Rojo; Irina Lazariciu; John Nesnas (Taylor & Francis Group, 2023)
Background Differences in atopic dermatitis (AD) disease course and manifestation with age may extend to treatment response. Objective To evaluate response maintenance with continuous-/reduced-dose abrocitinib or withdrawal and response to treatment reintroduction after flare in adolescent and adult participants in JADE REGIMEN (NCT03627767). Methods Adolescents (12-17 years) and adults with moderate-to-severe AD responding to abrocitinib 200-mg induction were randomly assigned to 40-week maintenance with abrocitinib (200 mg/100 mg) or placebo. Patients who experienced flare during maintenance received rescue treatment. Results Of 246 adolescents and 981 adults, 145/246 (58.9%) and 655/981 (66.8%), respectively, responded to induction. Similar proportions of adolescents and adults experienced flare during maintenance with abrocitinib 200 mg (14.9%/16.9%), 100 mg (42.9%/38.9%), and placebo (75.5%/78.0%). From the abrocitinib 200-mg, 100-mg, and placebo arms, respectively, Eczema Area and Severity Index response was recaptured by 28.6%, 25.0%, and 52.9% of adolescents and 34.3%, 33.7%, and 58.0% of adults; Investigator's Global Assessment response, by 42.9%, 50.0%, and 73.5% of adolescents and 34.3%, 50.6%, and 74.1% of adults. Abrocitinib had a similar safety profile regardless of age; nausea incidence was higher in adolescents. Limitations Adolescents represented 20% of the trial population. Conclusion Abrocitinib was effective in preventing flare in adolescents and adults.Clinicaltrials.gov listing: NCT03627767.